2014
DOI: 10.1371/journal.pone.0077974
|View full text |Cite
|
Sign up to set email alerts
|

25 Years after Vi Typhoid Vaccine Efficacy Study, Typhoid Affects Significant Number of Population in Nepal

Abstract: Salmonella Typhi, first isolated in 1884, results in infection of the intestines and can end in death and disability. Due to serious adverse events post vaccination, whole cell killed vaccines have been replaced with new generation vaccines. The efficacy of Vi polysaccharide (ViPS) vaccine, a new generation, single-dose intramuscular typhoid vaccine was assessed in Nepal in 1987. However, despite the availability of ViPS vaccine for more than 25 years, Nepal has one of the highest incidence of typhoid fever. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Children in this age group have high rates of typhoid fever. In addition, resistance to commonly used antibiotics continues to increase in south Asia and in Nepal [13]. The Vi vaccine pilot introduction project was developed with support from the IVI and implemented by the District Public Health Office of Lalitpur District, Kathmandu Valley, Nepal with a help of a non-governmental organization, MITRA Samaj between 2010 and 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Children in this age group have high rates of typhoid fever. In addition, resistance to commonly used antibiotics continues to increase in south Asia and in Nepal [13]. The Vi vaccine pilot introduction project was developed with support from the IVI and implemented by the District Public Health Office of Lalitpur District, Kathmandu Valley, Nepal with a help of a non-governmental organization, MITRA Samaj between 2010 and 2013.…”
Section: Resultsmentioning
confidence: 99%
“…It is recommended to people living in or visiting endemic areas and to control outbreaks [ 3 ]. Our study did not aim to review the efficacy of typhoid vaccine in preventing outbreaks, however we identified a couple of studies with outbreaks reported in vaccinated population [ 28 , 29 ] and similar studies have also been reported [ 30 ]. As observed from our review, we may say that in populations where vaccination does not prevent illness, it may delay the onset of symptoms thereby prolonging the incubation period.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cases have been accounted for all through the entire year. Like other Asian countries; typhoid fever can be a critical pointer of the financial state of the populace [12]. Sarwari & Sulaiman in 2007 reported about the worldwide the most notorious hotspots for typhoid fever are Pakistan, India, Nepal, Peru, Indonesia, Egypt and Mexico [13].…”
Section: Discussionmentioning
confidence: 99%